Oxypetalum lividum, a new species of Asclepiadoideae (Apocynaceae) from Peru - Farinaccio, Maria Ana; de Mello-Silva, Renato (Phytotaxa, 2013)
Oxypetalum lividum (Apocynaceae, Asclepiadoideae), a new species from the Department of San Martín, Peru, is here described and illustrated. Oxypetalum lividum is similar to O. weberbaueri, but it differs by its sessile, 1–5-florous inflorescences, pedicels 0.7–3.5 mm long, and flowers 9–11 mm long, which are borne on short pedicels 0.7–3.5 mm long; whereas O. weberbaueri has pedunculate, 10–20-florous inflorescences, pedicels 5–7 mm long, and flowers ca. 20 mm long. The bluish-green leaves of O. lividum may also distinguish it from all other species of the genus.